Age at First Child Does Education Delay Fertility Timing? The Case of Kenya - Ferre, Celine (2012)
Completing additional years of education necessarily entails spending more time in school. There is naturally a rather mechanical effect of schooling on fertility if women tend not to have children while continuing to attend high school or college, thus delaying the beginning of and shortening their reproductive life. This paper uses data from the Kenyan Demographic and Health Surveys of 1989, 1993, 1998, and 2003 to uncover the impact of staying one more year in school on teenage fertility. To get around the endogeneity issue between schooling and fertility preferences, the analysis uses the 1985 Kenyan education reform as an instrument for years of education. The authors find that adding one more year of education decreases by at least 10 percentage points the probability of giving birth when still a teenager. The probability of having one's first child before age 20, when having at least completed primary education, is about 65 percent; therefore, for this means a reduction of about 15 percent in teenage fertility rates for this group. One additional year of school curbs the probability of becoming a mother each year by 7.3 percent for women who have completed at least primary education, and 5.6 percent for women with at least a secondary degree. These results (robust to a wide array of specifications) are of crucial interest to policy and decision makers who set up health and educational policies. This paper shows that investing in education can have positive spillovers on health.